Caregiving demands and caregivers' psychological outcomes: the mediating role of perceived injustice. (March 2017) - Mohammadi, Somayyeh; de Boer, Maaike J; Sanderman, Robbert; Hagedoorn, Mariët
Objectives: This study hypothesized that higher caregiving demands are related to higher perceived injustice. Furthermore, this study investigated the mediating role of perceived injustice in the link between caregiving demands and caregivers' psychological well-being. Design: A cross-sectional design. Setting: The Pain Centre of the university medical centre. Subjects: Participants were 184 family caregivers of patients with chronic musculoskeletal pain. Main measures: Participants completed questionnaires that assessed caregiving demands (i.e. The Dutch Objective Burden Inventory), perceived injustice (i.e. The Injustice Experience Questionnaire), how much they considered different sources responsible for the injustice they experienced (i.e. A newly developed inventory), perceived burden (i.e. The Zarit Burden Interview), distress (i.e. The Depression, Anxiety, and Stress Scale), and anger (i.e. The Hostility subscale of the Symptom Checklist-90-Revised). Results: The findings showed that caregiving demands are significantly related to perceived injustice in family caregivers (r = .44; P < .001). Only a small group of family caregivers considered the patient or themselves responsible, but more than half of the caregivers considered healthcare providers at least somewhat responsible for the unjust situation. Finally, perceived injustice mediated the association between caregiving demands and burden (b = .11, CI: .04-.23) and distress (b = .05, CI: .006-.12), but not anger (b = .008, CI: -.01-.06). Conclusion: The findings suggest that perceived injustice plays an important role in the well-being of family caregivers and caregivers' well-being may be improved by changing their perceptions about their caregiving tasks and their condition.